Production and Optimization of Conjugated Linoleic and Eicosapentaenoic Acids by Bifidobacterium lactis in Cold-Pressed Soybean Cake - Azari, Samin Rafi; Hojjatoleslamy, Mohammad; Mousavi, Zeinab E.; Kiani, Hossein; Jalali, Sayed Mohammad Ali (Frontiers in Nutrition, 2022)
Background and Purpose: In regard to the biosynthesis of conjugated linoleic acid (CLA) and eicosapentaenoic acid (EPA) by some bacteria, the objective of this study was to evaluate the efficiency of solid-state fermentation based on soybean pressed cake (SPC) to produce CLA and EPA by Bifidobacterium lactis. The objective of this study was to evaluate the efficiency of solid-state fermentation based on SPC to produce CLA and EPA by Bifidobacterium lactis. Methods: Process conditions including humidity, inoculation level, and temperature parameters were optimized by adopting the RSM method and the design expert software. Accordingly, a homogeneous SPC paste substrate at 60, 70, and 80% humidity was prepared with different inoculation levels at 30, 37, and 44 ° C to assess the strain behavior. The introduced SPC consisted of 60% humidity, 2% inoculation level at 37 ° C, and 60% humidity, and 4% inoculation level at 30 and 44 ° C; it also included 6% inoculation level at 37 ° C, 70% humidity at 2% inoculation level, at 30 and 44 ° C, and 4% inoculation level at 37 ° C. Also, SPC with 80% humidity at 2% and 4% inoculation levels, and at 30 and 44 ° C was obtained. To confirm the accuracy of the conditions, an experiment was conducted according to the defined requirements. Results: The results were compared with the predicted data, which showed a significant difference. Under optimized conditions, with an inoculation level of 4% on the SPC medium with 70% humidity and at 37 ° C, Bifidobacterium lactis strains could yield 9cis-, 11 trans-linoleic and eicosapentaenoic at 0.18% and 0.39% of the total fatty acids. Conclusion: So, the potential benefits of using SPC as an inexpensive substrate for the commercial production of CLA and EPA should be noted.